ANALISIS RISIKO LUKA KAKI DIABETIK PADA PENDERITA DIABETES MELITUS DI POLIKLINIK DIABETES MELITUS DAN PENYAKIT DALAM - ERA DORIHI KALE; EMILIA ERNINGWATI AKOIT (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2015)
Diabetes mellitus (DM) is a group of heterogeneous disorders characterized by elevated levels of glucose in the blood. One complication that often occurs in people with diabetes mellitus is the occurrence of ulcers or sores on the feet. Diabetic foot injuries are an occurrence of infection, ulcer and/or deeper tissue damage associated with neurological and vascular disorders in the limbs of diabetics. This condition will lead to prolonged maintenance time, increased maintenance costs, increased disability rate, decreased quality of life and also increased the risk of death. Diabetic foot injuries can be prevented if detected risk levels from the beginning, but often do not get enough attention due to time constraints in carrying out the assessment. Currently developed a simple and simple screening tool so that handling can be done early to prevent further complications. The purpose of this study was to analyze the risk of diabetic foot wounds in patients with diabetes mellitus in Poliklink Diabetes Mellitus General Hospital Prof. Dr. W. Z. Yohannes Kupang. This research is a kind of quantitative research with descriptive study design. The sample of research in diabetes mellitus patients in Diabetes Mellitus Polyclinic General Hospital Prof. Dr. W.Z. Yohannes Kupang as many as 30 people selected by non-random with purposive sampling technique. The results showed that most people with diabetes mellitus have a lower risk of having a diabetic foot ulcer risk, but there is a risk of being even at high risk. Therefore, health education about foot care should still be given and improved so that the prevention of diabetic foot injuries become more optimal. In addition, the provision of information from nurses on the importance of foot screening every year for low-risk, while those at risk are recommended for screening every 6 months and who are at high risk are recommended for screening every 3 months.